An Analysis of the Antecedents of Positive Word-of-Mouth Communications with Regards to a Product or Service - Yee, Zi Cong (2010)
concept of word-of-mouth communications in the domain of marketing is not a new one. An extensive amount of research has been undertaken pertaining to the theoretical aspects of word-of-mouth communications. However, research in terms of its practical aspects is still scarce. Positive word-of-mouth regarding a product or service brings many benefits to a company, such as increased sales, but there has been a lack of research in identifying the motivating factors behind an individual’s willingness to spread positive wordof- mouth regarding a product or service provided by a company. Furthermore, rapid advancements in technology have led to the increased availability of broadband Internet access all around the world. In addition to this, the existence of social media networks such as Facebook has made it easier for individuals, and even customers of a product or service, to communicate with each other on the cyberspace. Such developments meant that positive word-of-mouth communications could no longer be viewed from a traditional perspective. In addressing these concerns, this dissertation has been undertaken to analyze the relationship between the antecedents of word-of-mouth communications and an individual’s tendency to engage in positive-word-of-mouth activities. In view of the rising availability of broadband Internet access to the masses, as well as the existence of Facebook, this dissertation will also seek to analyze the moderating effects presented by an individual’s usage level of Facebook towards the relationship between the antecedents of word-of-mouth communications and the tendency to engage in positive word-of-mouth activities